Android development on Android phone I - Lim, Chi Hau (2016)
Currently, almost everyone owns a smartphone and mobile applications impact humans seriously. Many types of mobile applications such as entertainment, social networks, utilities, shopping and many more have been used by humans almost everyday. Mobile applications can solve many problems and make our life more convenient. Hence, the objective of this project is to develop and implement a novel application that can be run on an Android smartphone. This project aims to develop a mobile application to assist people in solving problems of children/dementia patients/elderly people losing their way, parent/guardian unable to locate their current location and parent/guardian unable to know whether they reached/left the specified location or fail to reach/leave the location within a specified time. The implementation of this application was done using Android Studio IDE which is the official IDE for developing Android application. It provides an integrated environment for Android application development and using Java programming language and XML. Various libraries are also added for the Android application such as Volley and Javamail. All the data will be stored in server databases by using PHP programming and MySQL databases. Lastly, several forms of tests were conducted to identify bugs and defects of the app such as functional and user acceptance testing. Functional testing conducted by creates test case and identify the expected outcome of each test case. It helps to ensured all the functions implemented in the application are working and met requirements. User acceptance testing conducted via a survey form to evaluate user feedback and helps in further improvement of the application.